Ecclesia in Transitu, Di Antara Alfa dan Omega: GPI dan Notae Ecclesiae yang Baru - John Christianto Simon (Faculty of Theology Duta Wacana Christian University, 2023)
AbstractWhat are the pertinent indicators of the Church being lived by the GPI in the middle of a disruption related to its identity between oneness and independence, as well as the difficulties of the international context and nationality? is the question that this essay’s introduction poses. This article employs a qualitative approach to address this query, attempting to build a meaning for the church in the age of disruption by analytically interpreting the data obtained. The findings of this research demonstrate that GPI’s courage is walking with God to maintain the independence and unity of being a brother-sisterhood in God’s open banquet by fostering the concept of brother-sisterhood within its own body and assisting in the resolution of national and international problems. It is clear that GPI deserves to display the distinctive characteristics of the Church, including its commitment to multiculturalism, freedom, and Indonesian public liquidity. AbstrakTulisan ini dimulai dengan sebuah pertanyaan, apa tanda-tanda Gereja yang relevan dihidupi oleh GPI di tengah disrupsi terkait identitas dirinya di antara keesaan dan kemandirian, dan tantangan konteks globaldan kebangsaan? Untuk menjawab pertanyaan ini, pembahasan tulisan ini menggunakan metode kualitatif, dengan berusaha menginterpretasi secara analitis ke atas data-data yang ditemukan untuk mengonstruksi makna menggereja di era disrupsi. Hasil penelitian ini memperlihatkan bahwa keberanian (courage) GPI adalah berjalan bersama Allah untuk meneruskan keesaan dan kemandirian menjadi persaudaraan dalam perjamuan Allah yang terbuka dengan mengusung gagasan persaudaraan di tubuhnya sendiri dan turut mengatasi tantangan kebangsaan dan global hingga ke titik omega. Dapat disimpulkan bahwa GPI layak mengusung tanda-tanda Gereja yang khas, yaitu: persaudaraan, keesaan, kemandirian, multikultural dan keindonesiaan-kepublikan-kecairan.